2003
DOI: 10.1161/01.str.0000083394.33633.c2
|View full text |Cite
|
Sign up to set email alerts
|

Matrix and Bioabsorbable Polymeric Coils Accelerate Healing of Intracranial Aneurysms

Abstract: Background and Purpose— Acceleration of intra-aneurysmal clot organization and fibrosis may be a solution to preventing aneurysm recanalization after endovascular treatment. The purpose of this study was to evaluate the short-term efficacy and long-term safety of the new Matrix coil system. Methods— Matrix coils consist of thin platinum coils covered with a bioabsorbable, polymeric material (polyglycolic acid/lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(131 citation statements)
references
References 36 publications
3
126
0
2
Order By: Relevance
“…68 Many investigators have published scales that offer a rational, if not a validated basis, for assessing the performance of an implant, by giving points for features considered favorable for healing, including neck coverage with neointima, thickness of neointimal layer, or clot organization at the dome. 11,19,[43][44][45][46][47]56,69 These semiquantitative scales have largely been confined to single-center experiences; they have not been reproduced or validated. No one, to our knowledge, has been able to show that these criteria predict better in vivo clinical performances, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Many investigators have published scales that offer a rational, if not a validated basis, for assessing the performance of an implant, by giving points for features considered favorable for healing, including neck coverage with neointima, thickness of neointimal layer, or clot organization at the dome. 11,19,[43][44][45][46][47]56,69 These semiquantitative scales have largely been confined to single-center experiences; they have not been reproduced or validated. No one, to our knowledge, has been able to show that these criteria predict better in vivo clinical performances, however.…”
Section: Discussionmentioning
confidence: 99%
“…48 When all specimens showed permanent occlusions and favorable healing characteristics at some delayed time points, as seen in swine aneurysms, then some earlier timeframe was chosen, in hopes of detecting accelerated healing with some new material. 56 In the long term, treated canine lateral wall aneurysms are completely occluded in most cases. 7,41,[51][52][53]57 Canine bifurcation aneurysms have a propensity for recurrences, however; therefore, they can reproduce the problem found in human aneurysms.…”
Section: Pathologic Analyses Of Treated Aneurysmsmentioning
confidence: 99%
“…25 With these coils, aneurysm occlusion stability may be achievable even at VER of Ͻ 25%, and even large aneurysms may become candidates for successful embolization. Watanabe et al 26 have reported the hydrogel-coated coil as being a safe and feasible device for improving the packing efficacy in endovascular coil embolization.…”
Section: Possibility Of Use Of Bioactive Coils and Hydrogel-coated Coilsmentioning
confidence: 99%
“…Technological innovation continues with new coil designs incorporating bioactive materials such as fibroblast growth factor, 3,4 collagen, 5 and polyglycolic acid/lactide. 6 All of these materials have been shown to increase cellular response and healing potential in experimental aneurysms, and the widespread clinical use of Matrix coils 6 (Boston Scientific) has shown promising results in humans, although there have been anecdotal reports of an increase in embolic complications. The challenge of treating wide-necked and complex aneurysms has been the focus of balloon remodeling 7 and stent-assisted 8,9 techniques.…”
Section: Cerebral Aneurysm Therapymentioning
confidence: 99%